Pembangunan Sistem Administrasi Pendaftaran Pasien Rumah Sakit berbasis Android menggunakan Metode Scrum (Studi Kasus Rumah Sakit Marsudi Waluyo) - Muhammad Lavy Aunil Malik El Harisy; Komang Candra Brata; Adam Hendra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The hospital patient registration administration system is a system developed to expedite patient registration by minimizing data input errors, both from human error and system error. Agile is a flexible method of working. SCRUM is a framework and method for developing, delivering, and maintaining complex products, with an initial emphasis on software development. SCRUM is a suitable method for developing a system that must have efficiency in carrying out the data recording process. SCRUM incorporates known tools and techniques and can be applied in the best way that a developer can design to build a system. The first process that is carried out is a requirements analysis where functional requirements analysis, use case diagrams, use case scenarios, and non-functional requirements are carried out. After that, the system design is carried out. The contents include sequence diagrams, class diagrams, entity relationship diagrams, data design, and interface design. After the design phase is complete, implementation is carried out. In the process, researchers need to pay attention to the slightest changes that occur either internally or externally with the hospital. Recording is done in the form of iterations. After the implementation is complete, validity and usability testing is carried out. The total SUS score obtained is 1065 and the average value is 81.9231, has a good category and the system has acceptable status.